2006
DOI: 10.1093/nass/nrl108
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of auto-regulatory A-rich repeats found in the 5′-UTR of human PABP mRNA

Abstract: Eukaryotic poly(A)-binding protein (PABP) binds not only to the 3' poly(A) tail of most mRNAs, but also to the 5'-untranslated region (UTR). The latter form of binding leads to auto-regulation of PABP expression. The 5'-UTR sequence contains A-rich repeats different from that in 3'-UTR. The role of these A-rich repeats in auto-regulation, however, remains unknown. To confirm that the 5'-UTR sequence has a specific structure before or after PABP binding, and to determine the function of such structure, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 0 publications
0
13
0
9
Order By: Relevance
“…This structure shows that (rA) 11 forms a parallel doublestranded helix ( Figure 1) with symmetric base pairs formed by two adenine nucleotides (Figure 1 A). The A-A base pairs are "N7-amino-symmetric" where N7 atom of one adenine forms a hydrogen bond with the amino group of the opposite base.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…This structure shows that (rA) 11 forms a parallel doublestranded helix ( Figure 1) with symmetric base pairs formed by two adenine nucleotides (Figure 1 A). The A-A base pairs are "N7-amino-symmetric" where N7 atom of one adenine forms a hydrogen bond with the amino group of the opposite base.…”
mentioning
confidence: 98%
“…Subsequently, Pattabiraman [10] showed that formation of a parallel, right-handed nucleic acid duplex is thermodynamically favorable. Kikuchi et al [11] were able to crystallize A-rich fragments of RNA and DNA. Recently, Chakraborty et al, [12] using NMR spectroscopy and thermal denaturation studies, showed that poly(dA) can form a parallel homo duplex in acidic solution with low salt concentration.…”
mentioning
confidence: 99%
See 3 more Smart Citations